Experimental study of laminar and turbulent flow / Mohd. Effandy Mukhtar, Muhamad Nor Taufik Sahani and Shahirrunizan Majuan - Mukhtar, Mohd. Effandy; Sahani, Muhamad Nor Taufik; Majuan, Shahirrunizan (Faculty of Mechanical Engineering, 2002)
Laminar and turbulent flow is study about a fluid flow that involves some methodology like internal and external flow, fluid dynamic, and experiment analysis depends on limitations of our knowledge and facilities. The experimental study on fluid flow with respect to the Reynolds number, velocity profile, flow pattern, and others characteristics. The experiment apparatus are Osborne Reynolds Apparatus, GUNT HM150.11 Apparatus, and Airflow Bench Test Apparatus. Review of laminar and turbulent flow is presented first, followed by the description of the methodology employed, results and analysis, and finally the conclusion and recommendation.